Efficiency wages: Variants and implications - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
Higher wages increase labor costs but improve the productivity of the labor force through several channels. If firms take this into account and set their wages accordingly, the resulting wages may fail to adjust demand and supply but may engender phenomena like over-education, discrimination, regional wage differentials and a tendency for larger firms paying higher wages. All these phenomena are well established empirically. Efficiency wage theory provides an integrated explanation for them, rather than a sundry list of diverse reasons. At the same time, it provides an efficiency argument for progressive income taxation.
urn:nbn:de:bvb:19-epub-25168-8
Keywords: J24; J31; J63; J71; M52; D21; H21; H3; 330; efficiency wages; selection wages; turnover wages; discipline wages; shirking; size-wage effect; firm-size effect; congestion-wage effect; Reder-competition; discrimination; hiring standards; minimum wage; income taxation